Personality, self-esteem, and self-construal as correlates for forgiveness - Félix Neto (2004)
The relationship between forgivingness (enduring resentment, sensitivity to circumstances, and overall propensity to forgive) and a number of personality dimensions relevant to forgivingness was examined. These dimensions were self-esteem, shyness and embarrassment, on one hand, and self-construal and perceived loneliness, on the other hand. The main relationships between forgivingness and personality concerned the interpersonal dimensions of personality: shyness, embarrassment, independence from others, and interdependence with others. However, the intra-personal, strictly self-referential concomitants of these dimensions (self-esteem and loneliness) were not much linked to forgivingness. Furthermore, each personality factor had a distinct link with forgivingness: independence made the resentment still more enduring, shyness and social embarrassment exacerbated the sensitivity to circumstances, and interdependence increased the willingness to forgive. These findings throw light on the double aspect of forgiveness as intra- and inter-individual and on the relative independence of these aspects. The observed pattern of relationships varied notably (and significantly) as a function of the participants' genders. It could be therefore important, in future studies, to compute systematically correlation coefficients or assess main effects separately for women and men. Copyright (C) 2003 John Wiley Sons, Ltd.